PENGARUH PENAMBAHAN BAHAN ORGANIK PADA TANAH BEKAS TSUNAMI TERHADAP PERTUMBUHAN DAN PRODUKSI BEBERAPA VARIETAS KACANG HIJAU DI DESA BLANG KRUENG - Muhammad Hatta (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala, 2006)
Effect of Organic Matter in Tsunami Affected Land on Growht and Production of Several Varieties of Mung Bean at Blang Krueng Village Muhammad Hatta dan Nurhayati* Fakultas Pertanian Universitas Syiah Kuala Banda Aceh ABSTRACT The experiment was aimed at studying dosages of organic matter for growth and production of several varieties of mung bean in the tsunami affected land. The experiment was conducted atBlangKruengVillage, a tsunami affected area, from July to September 2006. The experiment applied factorial completely randomized design with three replicates. Two factors were studied, i.e. varieties and dosages of organic matter. Varieties were consisted ofGelatik, Parkit, and local while dosages were consisted of 0, 10, 20, and 30 t/ha. The results showed that varieties significantly afffected dried weight of grain per plot, but did not significantly affect other variables. Parkit variety had the best one. Dosages of organic matter did not significantly affect variables observed.